RETROSPECTIVE REPORTS IN ORGANIZATIONAL RESEARCH: A REEXAMINATION OF RECENT EVIDENCE. - MILLER, C. C.; CARDINAL, L. B.; GLICK, W. H. (Academy of Management Journal, 1997)
Background: Professionals who pursue a doctorate after significant post-baccalaureate work experience, a group we refer to as returners, represent an important but understudied group of engineering doctoral students.Returners are well situated to leverage their applied work experience in their advanced engineering training.Purpose/Hypothesis: We drew on results from the Graduate Student Experiences and Motivations Survey to explore the dimensionality of our scales measuring value and cost constructs.We used these scales, as well as measures of student expectancy of success, to compare returners with direct-pathway students.Design/ Method: We surveyed 179 returners and 297 direct-pathway domestic engineering doctoral students.We first conducted Exploratory Factor Analysis on our cost and value measures.We then used both Ordinary Least Squares and Ordinal Regression Model analyses to assess the relationships of various student characteristics and experiences (including returner status) with student expectancy of success and the emergent cost and values factors associated with doctoral study in engineering.Results: Factor analysis revealed three categories of values (interest, attainment, and career utility) that were largely consistent with those in Eccles' expectancy-value framework.A similar analysis identified three categories of costs (balance, financial, and academic) associated with pursuing a PhD.Returners felt significantly less confident in their ability to complete their degrees prior to enrolling and perceived higher levels of all cost types than direct-pathway students.Conclusions: Given the differences between returning and direct-pathway students, it is important to consider how universities might best recruit and retain returners.Tracking returner status could be critical in better supporting these students.